Lateral stress induced due root-water-uptake in unsaturated soils - Ali, Nazri (2012)
A two-dimensional (2-D) lateral stress was modeled as a result of matric suction change caused by vegetative induced moisture transfer. The negative pore-water pressures are estimated through governing partial differential equations for unsaturated soils. The results of the of simulated root water uptake are used as an input for the prediction of 2-D lateral stress in a stressdeformation analysis in an uncoupled manner. The soil is allow to expand and contract free laterally, as the as water is being abstracted from the soil. A mature Lime tree located on a Boulder clay subsoil for period covering a full spring/summer drying period was used as a case study. The result shows interdependence of lateral and vertical stress generated resulting from root water-uptake.